2001
DOI: 10.1088/0953-2048/14/8/307
|View full text |Cite
|
Sign up to set email alerts
|

Through-process study of factors controlling the critical current density of Ag-sheathed (Bi,Pb)2Sr2Ca2Cu3Oxtapes

Abstract: The connectivity and flux pinning components of the critical current density J c in a high-J c Pb) 2 Sr 2 Ca 2 Cu 3 O x (Bi-2223) composite throughout important steps in its thermomechanical treatment were investigated by mass density measurement, microstructural observation and extensive superconducting property characterization. The mechanical integrity of the filaments was greatest after the first heat treatment, because damage produced by intermediate rolling was not completely erased by subsequent heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…11,12 A significant amount of porosity, ϳ20% as indicated by mass density measurement, remains in multifilament 2223 tape after HT2 or FHT at 1 bar. 13,14 These residual cracks and porosity interrupt the grain connectivity and current paths, thus reducing J c . It is generally accepted that 2223 forms from 2212 and alkaline earth cuprate ͑AEC͒ phases in the presence of a transient liquid phase.…”
mentioning
confidence: 99%
“…11,12 A significant amount of porosity, ϳ20% as indicated by mass density measurement, remains in multifilament 2223 tape after HT2 or FHT at 1 bar. 13,14 These residual cracks and porosity interrupt the grain connectivity and current paths, thus reducing J c . It is generally accepted that 2223 forms from 2212 and alkaline earth cuprate ͑AEC͒ phases in the presence of a transient liquid phase.…”
mentioning
confidence: 99%
“…Poor inter-grain connectivity is one reason advanced for the less than optimum current carrying capacity [5], but prior magneto-optical reconstructions suggest that problems with connectivity have many sources. For example, even very high-multifilament Bi-2223 tapes can contain as much as 20% porosity [6]. Such pores, cracks and other detrimental microstructural features are at least partially caused by the multi-step thermomechanical treatment needed to react and to densify the starting Bi-2212 precursor as it converts toward a largely Bi-2223 phase assemblage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the filaments can dedensify when 2223 forms in HT2. It has been observed that even the best multifilamentary tapes still contain 10-30% porosity [3]. The pores and unhealed deformation damage from IR, which are inherent defects in the currently practiced conventional 2223 processing, destroy the Manuscript received August 6, 2002; revised October 7, 2002 integrity of grain connectivity, limiting supercurrent flow in the filaments.…”
Section: Introductionmentioning
confidence: 99%